The KNO3- and K2Co3-Induced hot corrosion behaviour of M-21 alloy at 900°C - Mohammed Misbahul, Amin; Mohammed Bello, Ahmad (Carl Hanser Verlag, 2009)
Link to publisher's homepage at http://www.materialography.de/PractMet/Archive/2008/index.php?id=g